1999
DOI: 10.1021/bi9901735
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the Agonist-Binding Sites of the Torpedo Nicotinic Acetylcholine Receptor:  Affinity-Labeling and Mutational Analyses Identify γTyr-111/δArg-113 as Antagonist Affinity Determinants

Abstract: Photoaffinity labeling of the Torpedo nicotinic acetylcholine receptor (nAChR) with [3H]d-tubocurarine (dTC) has identified a residue within the gamma-subunit which, along with the analogous residue in delta-subunit, confers selectivity in binding affinities between the two agonist sites for dTC and alpha-conotoxin (alpha Ctx) MI. nAChR gamma-subunit, isolated from nAChR-rich membranes photolabeled with [3H]dTC, was digested with Staphylococcus aureus V8 protease, and a 3H-labeled fragment was purified by reve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
71
2
1

Year Published

2000
2000
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(79 citation statements)
references
References 33 publications
5
71
2
1
Order By: Relevance
“…Some of the larger differences can be accounted for by the distinct buffer conditions used as follows: Hann et al (13) and Groebe et al (10) used low ionic strength buffers to measure binding in the presence of detergents. However, the data of Chiara et al (12) was carried out in physiological buffer that revealed affinities 5-10-fold higher than we observed. Our binding data on the mouse muscle AChR is in complete agreement with that of others (7).…”
Section: Table III Charge Effects On Binding Observed In Low Ionic Stcontrasting
confidence: 80%
See 3 more Smart Citations
“…Some of the larger differences can be accounted for by the distinct buffer conditions used as follows: Hann et al (13) and Groebe et al (10) used low ionic strength buffers to measure binding in the presence of detergents. However, the data of Chiara et al (12) was carried out in physiological buffer that revealed affinities 5-10-fold higher than we observed. Our binding data on the mouse muscle AChR is in complete agreement with that of others (7).…”
Section: Table III Charge Effects On Binding Observed In Low Ionic Stcontrasting
confidence: 80%
“…At the Torpedo AChR ␦-subunit, acetylation of Lys-10 does appear to cause an increase in affinity of 2-4-fold, consistent with lessened repulsion. However, this change is much smaller than the 1000-fold effect observed by Chiara et al (12). Our data suggest that the ␦Arg-113 interaction is not through electrostatic repulsion at the N terminus, His-5, or Lys-10 of Ctx.…”
Section: Table III Charge Effects On Binding Observed In Low Ionic Stcontrasting
confidence: 70%
See 2 more Smart Citations
“…Tyr 141 , Tyr 143 , and Tyr 153 align with residues in the nACh receptor binding loop E. Extensive studies on the nACh receptor and the ␥-aminobutyric acid A receptor have indicated the importance of residues within this binding loop as determinants of antagonist affinity (31)(32)(33)(34)(35)(36). The lack of sequence conservation in this region in particular is thought to confer the differences in antagonist selectivity.…”
Section: Discussionmentioning
confidence: 99%